Observations on some reproductive features of Carasobarbus luteus (Heckel, 1843) from the Shatt Al-Arab River, Southern Iraq - Abdullah, A.H.J.; AI-Noor, S.S. (Mesopotamian Journal of Marine Sciences, 2022)
The present study was conducted from December 2013 to November 2014 to investigate the reproductive features of Himri Carasobarbus luteus in the Northern reaches of Shatt Al-Arab river in Southern Iraq. The samples were collected using seine, gill, cast nets as well as electrofishing. A total of 351 specimens from himri were caught but only mature individuals were chosen to estimate the absolute and relative fecundity and egg diameters. The results of the present research revealed that the highest GSI values were recorded in male and female (4.63 and 11.99) during the April month. Absolute fecundity was increased with length, weight and gonads weight, and it was ranged as 2098 eggs for 131 mm total length and 35 g weight to 14147 eggs for 209 mm total length and 131 g weight. Relationship between length, weight and reproductive parameters were highly significant. A highest relative condition factor of females (1.24) was calculated in March 2014.